Case Study: Open Pyometra in a Pomeranian Dog at INI Veterinary Service Clinic - Kristanto, Dwi; Nur Aini, Dina Wahyu; Willyanto, Iwan; Prasetyo, Dodik; Rickyawan, Nofan (Media Kedokteran Hewan, 2024)
A five-year-old female Pomeranian dog presented with vomiting, restlessness, decreased appetite, and vaginal discharge. The physical examination revealed yellowish to brownish purulent vaginal discharge with an unpleasant smell. The X-ray image showed an enlarged uterus, while the hematology results revealed hypochromic normocytic anemia, neutrophilia, lymphopenia, and thrombocytopenia. The blood chemistry test results showed abnormalities, including elevated levels of alkaline phosphatase levels (ALP) and cholesterol as well as decreased amylase levels. Based on the anamnesis, clinical findings, physical examination, and supporting examinations, it was concluded that the dog was diagnosed with open cervix pyometra. The dog was treated with oxytocin hormone at a dose of 0.5 IU/kg BW, methylergometrine at a dose of 0.125 mg/dog, enrofloxacin at a dose of 5 mg/kg BW, carprofen at a dose of 2.5 mg/kg BW, cyproheptadine at a dose of 0.5 mg/kg BW, ranitidine at a dose of 3.5 mg/kg BW, ondansetron at a dose of 1 mg/kg BW, glyseryl guaiacolate at a dose of 20 mg/kg BW, ambroxol HCl at a dose of 2 mg/kg BW, Fufang® at adose of  1 ml, Sangobion® at a dose of 100 mg/dog, Maxbiotik® at a dose of 66 mg, and Transfer Factor Plus® at a dose of 20 mg. The treatment resulted in an improvement in the animal's condition as evidenced by the absence of nasal and vaginal discharges and vomiting, as well as a stool consistency of two out of five.